Peran Amicus Curiae pada Putusan Hakim Terhadap Justice Collaborator dalam Perkara Tindak Pidana Pembunuhan Berencana - Tombokan, Nevri Berti; Gultom, Potler; Sudarto, Sudarto (Neolectura, 2024)
Amicus Curiae is limited to providing opinions, and not taking action. The practice of amicus curiae is actually commonly used in countries that use the Common Law system and not the Civil Law system adopted by Indonesia. However, this does not mean that this practice has never been applied or practiced in Indonesia. In the Indonesian judiciary, amicus curiae has not been clearly regulated, but the legal basis for accepting the concept of amicus curiae in Indonesia is Article 5 Paragraph (1) of Law Number 48 of 2009 concerning Judicial Power. Therefore, it is interesting to examine the role of the amicus curiae in the judge's decision regarding the justice collaborator in the criminal case of premeditated murder. To answer these problems, normative legal research methods (normative juridical) are used with a statutory approach, case approach, conceptual approach and comparative approach, using secondary data obtained from primary, secondary and tertiary legal material sources. In this research, the role of the amicus curiae in the judge's decision on the justice collaborator in the criminal case of premeditated murder as regulated in Article 340 of the Criminal Code. Apart from that, the role of amicus curiae is also regulated in the Constitutional Court Regulations Article 14 Paragraph (4) Number 06/PMK/2005, Article 180 Paragraph (1) KUHAP, Article 183 KUHAP, Article 89 Paragraph (3) Law Number 39 of 1999 concerning Human Rights Humans, Circular Letter of the Supreme Court of the Republic of Indonesia (SEMA) Number 4 of 2011, even though they do not have clear regulations, in their application amicus curiae have never been prohibited by judges.